Students Motivation in Higher Vocational Education System: Petrozavodsk State University. / Motivación de los estudiantes en el sistema de educación vocacional superior: Universidad Estatal de Petrozavodsk. - BLAZHEVICH, L. E.; NIKITINA, K. A.; RODIONOVA, O. A.; SMIRNOVA, O. E. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research is devoted to studying the motivation of students to continue their education in the higher education system - in the magistracy, graduate school and the system of additional postgraduate professional education.During the study, first-year and fourth-year students of the Institute of Physical Culture, Sports and Tourism of Petrozavodsk State University were interviewed. The relevance of this research paper is to identify the main motivesamong junior and senior students for continuing their education, taking into account the socio-economic situation in the Russian Federation and in the world at the moment.RESUMEN Esta investigación está dedicada a estudiar la motivación de los estudiantes para continuar su educación en el sistema de educación superior, en la magistratura, la escuela de posgrado y el sistema de educación profesional adicional de posgrado. Durante el estudio, los estudiantes de primer y cuarto año del Instituto de Cultura Física, Deportes y Turismo de la Universidad Estatal de Petrozavodsk fueron entrevistados. La relevancia de este trabajo de investigación es identificar los principales motivos entre los estudiantes júnior y sénior para continuar su educación, teniendo en cuenta la situación socioeconómica en la Federación de Rusia y en el mundo en este momento.